Humanitarianism as debt: Germany and its Traumatic Memory (2022)
Angela Merkel’s decision to unreservedly open her country’s borders in 2015 to hundreds of thousands of refugees represents one of the most significant events in the history of Germany in the 20th century. Both the Chancellor’s determination and the attitude expressed by the majority of the citizens must be interpreted in the context of a history characterized both by the suffering inflicted by Germans and by their own suffering as a result of the war conflicts in which they were involved. In this respect, German humanitarianism after 1990 owes, in part, a debt to the past: either as restitution for the harm done or as a reminder of the pain suffered. For decades, fields as diverse as political discourse and literature contributed to shaping a cultural memory that focused on 20th century trauma and on national responsibilities that had not yet been fulfilled.